The Role of Expectancy Theory in Improving Research Performance: The Case of Midwifery Lecturers - Astyandini, Budi; Pramono, Suwito Eko; Pudjiastuti, RR Sri Endang; Yulianto, Arief (Proceedings of International Conference on Science, Education, and Technology, 2024)
Lecturers need motivation to conduct research that serves as the best teaching material for students. However, in the educational sector, common issues such as lack of motivation, inadequate information systems, and weak supervision often result in poor research performance. This study aims to examine the simultaneous influence of motivation, information systems, and supervision on the research performance of lecturers. The study involved 78 lecturers from the midwifery department. A quantitative approach was employed, using validated questionnaires and multiple regression analysis. The results indicate that Information systems (X1) has a t-value of -4.106, which is greater than the t-table value of 1.9917, with a significance level of 0.000 < 0.05, indicating a positive and significant effect on research performance (Y). Supervision (X2) have a t-value of 3.531, exceeding the t-table value of 1.9917, with a significance level of 0.001 < 0.05, indicating a negative and significant effect on research performance (Y). motivation (X3) has a t-value of 4.719, greater than the t-table value of 1.9917, with a significance level of 0.000 < 0.05, indicating a positive and significant effect on research performance (Y). The F-value is 42.037, exceeding the critical value of 3.1203, with a significance level of 0.000 < 0.05, showing a significant simultaneous effect of these variables on research performance. The key finding of this study is that lecturers' research performance needs to be supported by effective information systems, high motivation, and robust supervision to enhance research quality and productivity.